NEONATAL DYNAMICS OF NEURON-SPECIFIC ENOLASE IN NEWBORNS WITH POSTHYPOXIC ENCEPHALOPATHY - Sadigova, Sh.A. (World of Medicine and Biology, 2023)
The purpose of the study was to determine the informativeness of neuron specific enolase in prediction of the course of posthypoxic encephalopathy in newborns. 68 newborns with posthypoxic encephalopathy were included in the study (main groups): group I – 41 premature children (28–36 weeks of gestation), divided into 2 subgroups: subgroup IA (n=19; 28–31 weeks of gestation), subgroup IB (n=22; 32–36 weeks of gestation); group II – 27 full-term children (37–40 weeks of gestation). The control group consisted of 29 children without perinatal asphyxia. Neurosonography and determination of neuron specific enolase in blood serum were performed in dynamics of neonatal period. According to results, compared to the control group, the concentration of neuron specific enolase was higher in children with perinatal asphyxia, the highest level was noted in group IB. The levels of neuron specific enolase in the dynamics of the early neonatal period (days 1–3; 5–7) was twice as high in newborns of subgroups with structural changes of the brain, compared to subgroup without structural changes on neurosonography. Thus, it is obvious, that neuron specific enolase can be used in practice to predict the course of posthypoxic encephalopathy.
Keywords: perinatal asphyxia; newborns; neuron specific proteins; neurosonography; neonatal brain damages